1996
DOI: 10.1007/bf01464075
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, cognitive, and metacognitive influences on text revision: Assessing the evidence

Abstract: To assess progress in understanding text revision, we review research reported since 1980, when process analyses of writing were beginning (Fitzgerald, 1987). A modernized version of the revision model by Flower, Hayes, Carey, Schriver, and Stratman (1986)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
10

Year Published

1997
1997
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 112 publications
(196 reference statements)
2
75
1
10
Order By: Relevance
“…Butterfield, Hacker et Alberston (1996) complètent le processus de révision Butterfield et al (1996) complètent des aspects restés implicites dans le modèle de révision de Flower et al (1986) en distinguant clairement la mémoire à long terme et la mémoire de travail et, au sein de cette dernière, les niveaux cognitifs des niveaux métacognitifs. Ce modèle est évoqué ici car la capacité des rédacteurs à contrôler ce qu'ils font constitue une part importante de l'expertise rédactionnelle (Piolat, 1998 Leur modèle de la révision de texte est constitué de deux composants (cf.…”
Section: Exé C Ution Contrôle Formulationunclassified
“…Butterfield, Hacker et Alberston (1996) complètent le processus de révision Butterfield et al (1996) complètent des aspects restés implicites dans le modèle de révision de Flower et al (1986) en distinguant clairement la mémoire à long terme et la mémoire de travail et, au sein de cette dernière, les niveaux cognitifs des niveaux métacognitifs. Ce modèle est évoqué ici car la capacité des rédacteurs à contrôler ce qu'ils font constitue une part importante de l'expertise rédactionnelle (Piolat, 1998 Leur modèle de la révision de texte est constitué de deux composants (cf.…”
Section: Exé C Ution Contrôle Formulationunclassified
“…(3) The execution process allows the subject to write the verbal message on a sheet of paper or a computer screen, controlling his or her graphomotor movements on the basis of visual and kinesthetic feedback (Graham & Weintraub, 1996;Smyth & Silvers, 1987). (4) Because the resulting text is rarely a perfect first draft, the revision process involves reading the text produced so far in order to assess it and, if necessary, reengage the writing processes in order to modify its form and/or content (Butterfield, Hacker, & Albertson, 1996;Hayes, Flower, Schriver, Stratman, & Carey, 1987).…”
mentioning
confidence: 99%
“…Possibly the focus on indicators of time and place also provided the students a window to other sentence formulation and editing issues that deserve attention in revision. In studies into young students' revisions, it is observed that their attention is often restricted to formal issues (spelling or grammar) rather than to meaning related issues (Butterfield, Hacker & Albertson, 1996;. The results of this study suggest that instruction in the use of specific linguistic means helps students paying attention to the importance of linguistic features in a more general sense, including both meaning and form aspects of their texts at the same time.…”
Section: Conclusion and Discussionmentioning
confidence: 74%
“…For example, students find it difficult to detect problems in their texts, if there is no one pointing at such problems from a readers' perspective. In addition, given the complexity of issues involved in coherent writing, and students" poor linguistic-and genre knowledge, their attention is directed to issues of spelling or punctuation rather than to meaning related issues (Butterfield, Hacker & Albertson, 1996;. Even, when they make meaning related changes, these often turn out to be of small consequence or make matters even worse (Bereiter & Scardamalia, 1987;Chapman, 2006;Fitzgerald, 1987;Sommers, 1980;Van Gelderen, 1997).…”
Section: Writing With Peer Responsementioning
confidence: 99%
See 1 more Smart Citation